Development of Botryodiplodia rot of guava fruits in relation to temperature and humidity - V.N. PATHAK, K.D. PATEL and (Indian Phytopathology, 2002)
Temperature and per cent relative humidity (% RH) are known to exert a powerful influence on fruit rots. These factors may retard ripening process that may increase the fruit defences. Apart from this, these factors may also affect various physiological processes of the pathogen during infection and pathogenesis. The information on this aspect is not available in respect of Botryodiplodia rot of guava fruits. This paper reports influence of temperature and relative humidity on disease severity, sporegermination and activities of cell wall degrading enzymes (CWDE) of the pathogen.